Business stressors, family-business identity, and divorce in family business: A vulnerability-stress-adaptation (VSA) model. Issue 3 (September 2018) - Sanchez-Ruiz, Paul; Maldonado-Bautista, Ileana; Rutherford, Matthew
Abstract: A considerable amount of research focuses on how divorce in enterprising families influences family business outcomes. Yet, the impact that family businesses have on the divorce of enterprising families remains relatively under-researched. We contribute to the emerging enterprising family heterogeneity literature by building upon the Vulnerability-Stress-Adaptation (VSA) model and explore two questions regarding the influence of family businesses on divorce: Do family business-related stressors influence divorce? And, if so, what adaptive processes help enterprising families to cope with family business-related stressors? We hypothesize that high levels of debt and high sales revenue levels (as stressors) positively and significantly affect the rate of divorce in family businesses. In addition, we contend that a strong identity alignment between family and business moderates the stressors-divorce relationship, reducing the divorce rate. Our empirical assessment of divorce in family businesses employs two large cross-sectional data sets—the 1997 (N = 2495) and 2002 (N = 583) American Family Business Surveys. 1 Overall, we find that our stressors do increase the rate of divorce, but this can be mitigated by identity alignment.